INNOVATIVE METHODS OF TEACHING ENGLISH - Pulatova Shakhzoda Haydarovna; Tolibova Nodira Nosirovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article highlights various methods of teaching English, and also describes the use of innovative methods for teaching students to communicate in English. New methods such as group discussions, role-playing, brainstorming, etc. help students improve their confidence in the process of communicating in English.